The Impact of PSR™ (Plant Small RNA Technology), Tea Extract, and Its Principal Components on Mitochondrial Function and Antioxidant Properties in Skin Cells - Marielle Moreau; Tanesha Naiken; Gérard Bru; Clarisse Marteau; Laurence Canaple; Lorène Gourguillon; Emmanuelle Leblanc; Elodie Oger; Audrey Le Mestr; Joel Mantelin; Isabelle Imbert; Carine Nizard; et al. (Cosmetics, 2023)
Objective: This study explored the impact of a black tea extract obtained through (plant small RNA) PSRTM technology, characterized by its abundance of small molecules, particularly citric acid—an antioxidant and tricarboxylic acid (TCA) cycle contributor—on mitochondrial health. The primary focus was to assess whether this extract could counteract reactive oxygen species (ROS)-induced mitochondrial alterations associated with aging, which lead to impaired mitochondrial function, reduced ATP production, and increased ROS generation. Methods: The PSRTM extraction method was employed to obtain a high content of polyphenols and small molecules, particularly citric acid. Results: In comparison with a conventional extract, the PSRTM extract demonstrated significant enhancements in aconitase activity, an ROS-sensitive enzyme in the TCA cycle, as well as basal respiration and ATP synthesis in fibroblast cells and skin biopsies. Moreover, the PSRTM extract effectively reduced ROS production by safeguarding this critical enzyme within the Krebs cycle and displayed superior capabilities in scavenging free radicals when exposed to UV-induced stress. When administered post-UV exposure, the PSRTM extract protected nuclear DNA by reducing the formation of cyclobutane pyrimidine dimers (CPDs) and promoting DNA repair mechanisms. Furthermore, the extract exhibited beneficial effects on the extracellular matrix, characterized by a reduction in matrix metalloprotease 1 (MMP1) and an increase in fibrillin 1 expression. Conclusions: These findings collectively suggest that the PSRTM extract holds promising antiaging potential, potentially functioning as a mitochondrial nutrient/protector due to its multifaceted benefits on mitochondrial function, nuclear DNA integrity, and the extracellular matrix.